Networks and netwars : the future of terror, crime, and militancy - Arquilla, John; Ronfeldt, David F. (MR (Series), 2001)
Netwar is the lower-intensity, societal-level counterpart to the editors' earlier, mostly military concept of cyberwar. This volume studies major instances of netwar that have occurred over the past several years--from Osama bin Laden's networked terrorists to the Battle of Seattle's social activists--and finds, among other things, that netwar works very well. Whether the protagonists are civil-society activists or uncivil-society criminals and terrorists, their netwars have generally been successful. Strategists and policymakers in Washington, and elsewhere, have already begun to discern the dark side of the netwar phenomenon, especially as manifested in terrorist and criminal organizations. In this volume, the editors and their colleagues examine various types of netwar, from the most violent to the most socially activist. In doing so, they find that, despite the variety, all networks that have been built for waging netwar may be analyzed in terms of a common analytic framework. There are five levels of theory and practice that matter--the technological, social, narrative, organizational, and doctrinal levels. A netwar actor must get all five right to be fully effective. The most potent netwarriors will not only be highly networked and have the capacity for mounting "swarming" attacks, they will also be held together by strong social ties, have secure communications technologies, and project a common story about why they are together and what they need to do. These will be the most serious adversaries. But even those networks that are weak on some levels may pose stiff challenges to their nation-state adversaries. With this in mind, it is necessary to go beyond just diagnosing the nature of the networked nonstate opponent in a given conflict. It will become crucial for governments and their military and law enforcement establishments to begin networking themselves